We, the City: Plurality and Resistance in Berlin and Istanbul - İnal-Çekiç, Tuba; Woźniak, Urszula Ewa (De Gruyter, 2022)
Given their unchecked neoliberal restructuring, Berlin and Istanbul have been exposed to various forms of political polarisation and social injustice over the last decade. As a result, the struggle for affordable housing, access to public space, fair working conditions, ecological justice and the right to different ways of life has intensified. Various forms of resistance "from below" have challenged the relationship between local governments and social movements, questioning where and how the city's political problems arise. In a mixture of dialogues, essays and critical reflections, this book explores the ways in which residents of Berlin and Istanbul experience, express and resist the physical, political and normative reorganisation of their cities. It poses the question: Who is the We in We, the City?